The effects of irrational gambling beliefs on game preference types and participation attitudes: Focusing on university students - Choi, Eun-Mi; Jin, Chan Ho (Edelweiss Applied Science and Technology, 2025)
This study investigates the influence of irrational gambling beliefs on game preference types and participation attitudes among university students in South Korea. A structured questionnaire survey was conducted with 179 participants, and statistical analyses were performed using SPSS 21.0. The research model includes three hypotheses examining the relationships between irrational gambling beliefs, game preferences, and gambling participation attitudes. The findings indicate that irrational gambling beliefs, particularly overconfidence and skill overestimation, significantly affect game preference types. Game preference types also show a substantial impact on participation attitudes, while skill overestimation has a stronger influence on deep participation attitudes than overconfidence. The results suggest the need for educational programs that correct gambling misconceptions and promote responsible gaming behavior. Additionally, attention should be given to the growing prevalence of Hold’em pubs and the need for stricter regulation and student awareness. This study provides practical insights for university administrators, policymakers, and mental health professionals to develop proactive strategies for preventing gambling addiction in young adults. The findings contribute to the growing body of literature on gambling behavior and provide empirical evidence to support preventive measures in university settings.